The Middle East and Islamic world reader - Gettleman, Marvin E.; Schaar, Stuart (Grove Press, 2003)
Traces the history of the core Islamic lands from their Golden Age to today, revealing the Muslim world's multi-faceted societies, political systems, key figures, and relationships with outside groups